The Asset-By-Asset Poverty Index - Mtapuri, Oliver (Journal of Income Distribution®, 2012)
This article pioneers an asset-by-asset point index, which represents a simple methodology that uses inputs rather than outputs of well-being to recognise the 'poor' on a point basis, household by household. It focuses on assets, which are a significant aspect of well-being in whose absence households may fall into deprivation. The index is well-suited for the production of localised indicators, as it allows disaggregation of data by a rural/urban divide and even at the village/household level, which facilitates area-based interventions. It is an asset-based measure, which will help to identify the poor and the type of help they need; it can thus be used as a monitoring tool at the household and community level. It represents an alternative approach to measuring household poverty.